An adaptive signal compression system with pre-specified reconstruction quality and compression rate - TÜMER, MUSTAFA BORAHAN (ELSEVIER IRELAND LTD, 2006)
Two essential properties of a signal compression method are the compression rate and the distance between the original signal and the reconstruction from the compressed signal. These two properties are used to assess the performance and quality of the method. In a recent work [B. Tumer, B. Demiroz, Lecture Notes in Computer Science-Computer and Information Sciences, volume 2869, chapter Signal Compression Using Growing Cell Structures: A Transformational Approach, Springer Verlag, 2003, pp. 952-959], an adaptive signal compression system (ACS) is presented which defines the performance of the system as a function of the system complexity, system sensitivity and data size. For a compression method, it is desirable to formulate the performance of the system as a function of the system complexity and sensitivity to optimize the performance of the system. It would be further desirable to express the reconstruction quality in terms of the same system parameters so as to know up front what compression rate to end up with for a specific reconstruction quality. In this work, we modify ACS such that the modified ACS (MACS) estimates the reconstruction quality for a given system complexity and sensitivity. Once this relation is identified it is possible to optimize either compression rate or reconstruction quality with respect to system sensitivity and system complexity while limiting the other one. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: adaptive signal compression; growing cell structures; regression analysis; cardiovascular diseases; GROWING CELL STRUCTURES; ECG; ALGORITHM; NETWORK